(untitled) (International Journal of Ayurveda and Pharma Research, 2015)
Wrightia tinctoria R.Br. (Apocyanaceae) is considered to be therapeutically very effective jaundice plant in Indian indigenous system of medicine. The juice of the tender leaves is used efficaciously in jaundice. The plant is known to be used for psoriasis and other skin diseases. In the present study, the chemical composition of the essential oil from the leaves of Wrightia tinctoria was analyzed by GC-MS (Gas Chromatography-Mass Spectrometry). GC-MS analytical technique provides conclusive confirmatory evidence for the identification and characterization of essential oil components. Thirty seven known compounds have been identified and quantified from the leaf essential oil of Wrightia tinctoria by GC-MS analysis. The major compounds present in the leaf essential oil are urs-12-en-24-oic acid-3-oxo-methyl ester (34.28%), hydroquinone (13.24%), 1, 6-cyclodecadiene,1-methyl-5-methylene- 8- (1-methylethyl) (9.70%), 3-methyl-2-(2-pentenyl)- 2-cyclopentene-1-one (6.76%) and 9, 12, 15-octadecatrienoic acid (4.52%). This is the first report of extraction of essential oil from the leaves of Wrightia tinctoria.